2015 European guidelines for the management of partners of persons with sexually transmitted infections. (7th May 2015) - Tiplica, G.‐S.; Radcliffe, K.; Evans, C.; Gomberg, M.; Nandwani, R.; Rafila, A.; Nedelcu, L.; Salavastru, C.
Abstract Background Partner management is the process of identifying the contacts of a person infected by a sexually transmitted infection (STI) and referral to a health care provider for appropriate management. It represents a public health activity. Methods This guideline is produced by the IUSTI European Guideline Editorial Board and EDF Guideline Committee. Results It provides recommendations concerning the infections that require partner management, the lookback periods for this STI and the main steps to follow for partner management (offering support to patients, notifying partners, identification of contacts). Partner management is voluntary and needs to be performed with respect to human rights, social, cultural and religious behaviours. Conclusions In European countries, there are different approaches to the partner management; some common type of actions can enhance the fight against STI.